Hopes and uncertainties in the nightlife industry of post-COVID-19 Europe - Nofre,Jordi (2020)
Abstract From the 1990s until the pre-COVID-19 outbreak, commercial nightlife has become central to the urban branding, and tourism marketing strategies of many European cities. However, the night-time leisure industry has stalled in Europe as a consequence of the COVID-19 pandemic and the unprecedented lock-down and physical distancing measures imposed by several national governments. This short paper aims to picture the uncertain scenario that the nightlife industry of Europe, and Portugal, might have to face in post-pandemic times.